1996
DOI: 10.1097/00042560-199604010-00005
|View full text |Cite
|
Sign up to set email alerts
|

Initial Studies on Active Immunization of HIV-Infected Subjects Using a gp120-Depleted HIV-1 Immunogen: Long-Term Follow-Up

Abstract: In 1987, exploratory clinical studies were initiated to determine whether the development of AIDS in HIV-infected individuals might be delayed or prevented by immunization with an inactivated HIV preparation. Preclinical studies had shown the preparation to be safe and immunogenic. Twenty-three patients with biopsy-confirmed persistent generalized lymphadenopathy (CDC III) and two with asymptomatic HIV infection and CD4 lymphocyte counts between 135 and 769/mm3 were studied, of whom eight (32%) had additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…The results presented in this report confirmed the results of previous studies with the HIV-1 immunogen in terms of its ability to augment CD4-cell numbers and HIV-1-specific immune function in asymptomatic subjects not taking antiviral drug therapy (19,38,39). Furthermore, the augmentation of absolute CD4-cell numbers observed in this study is in contrast to the lack of beneficial effects observed with gp160 or gp120 therapeutic vaccines (11,14,34).…”
Section: Discussionsupporting
confidence: 89%
“…The results presented in this report confirmed the results of previous studies with the HIV-1 immunogen in terms of its ability to augment CD4-cell numbers and HIV-1-specific immune function in asymptomatic subjects not taking antiviral drug therapy (19,38,39). Furthermore, the augmentation of absolute CD4-cell numbers observed in this study is in contrast to the lack of beneficial effects observed with gp160 or gp120 therapeutic vaccines (11,14,34).…”
Section: Discussionsupporting
confidence: 89%
“…Further problems associated with such treatments include toxicity and side effects, high cost, development of viral resistance, and low efficacy owing to viral genotype specificity/ patient variables (11,43,61,101,108,121,145,157,171). Efforts to develop conventional vaccines for HIV have been hampered by potential pathogenicity and poor capacity to elicit protective immune responses (6,54,80,162). Several new vaccination approaches for HIV (e.g., DNA and viral vectors) are in clinical trials (3,4,7,23,82,105,133,146).…”
Section: Tetraspanins As Potential Therapeutic Targets For Viruses Thmentioning
confidence: 99%
“…The different sites used for the sequential DNA priming, as well as two sequential protein boost inoculations, enabled the clinical separation of DTH-like reactions from local reactions induced by QS21 as reported in a previous HIV Env-QS21 vaccine study [10]. DTH reactions have been reported in other vaccine studies involving prophylactic vaccines against HIV [16], syphilis [17] and malaria [18], and a therapeutic vaccine for HIV [19]. A previous detailed report of exaggerated skin reactions following re-administration of gp160 in HIV+ subjects was attributed to contaminating insect cell proteins [20], and is not similar to our observations of DTH or vasculitis.…”
mentioning
confidence: 91%